Smart decisions in complex systems - Massotte, Pierre; Corsi, Patrick (ISTE, Ltd. ; Wiley, 2017)
Faced with ever-increasing complexity on a daily basis, the decision-makers of today are struggling to find the appropriate models, methods and tools to face the issues arising in complex systems across all levels of global operations. Having, in the past, resorted to outdated approaches which limit problem-solving to linear world views, we must now capitalize on complexities in order to succeed and progress in our society. This book provides a guide to harnessing the wealth inherent to complex systems. It organises the transition to complex decision-making in all business spheres while providing many examples in various application domains.